Convergence between clinician‐rated and patient‐reported PTSD symptoms in a specialized outpatient service: The moderator role of gender. Issue 2 (27th August 2020) - Ferretti, Fabio; Gualtieri, Giacomo; Bossini, Letizia; Olivola, Miriam; Del Matto, Laura; Desantis, Serena; Fagiolini, Andrea; Pozza, Andrea; Coluccia, Anna
Abstract: Purpose: Posttraumatic stress disorder (PTSD) includes different symptoms: re‐experiencing, avoidance of reminders and numbing, and hyperarousal. Although questionnaires are widely used, clinician‐administered interviews provide a more comprehensive exploration of symptoms. Few studies examined the convergence between clinician‐rated and patient‐reported general severity and symptoms, with mixed findings. We explored the association between clinician‐rated and patient‐reported general severity and symptoms and the moderator role of gender in PTSD patients referred to a specialized outpatient service. Design and Methods: The Clinician‐Administered PTSD Scale and Davidson Trauma Scale were administered to 56 patients. Findings: Patients classified by clinicians as with higher avoidance/numbing symptoms and women classified with higher hyperarousal symptoms reported higher general severity. Practice Implications: The assessment of the patients reporting high severity should focus on hyperarousal, particularly for women.